2015
DOI: 10.1155/2015/767945
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Cefquinome Nanoparticles by Using the Supercritical Antisolvent Process

Abstract: The supercritical antisolvent process was used successfully to prepare nanoparticles of cefquinome. These particles were observed by scanning electron microscope (SEM) and their average diameter was measured by laser particle size analyzer. In the experiments, dimethyl sulfoxide (DMSO) was selected as solvent to dissolve cefquinome sulfate. It was confirmed by orthogonal experiments that the concentration of solution was the primary factor in this process followed by feeding speed of solution, precipitation pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…It confirmed that the -carotene that dissolved in DCM solvent was not change after recrystallization process by SCCO2. Like the particle formation from other chemical compounds by SCCO2 antisolvent [24][25][26], the particles formation from -carotene solution by SCCO2 antisolvent may be affected by the feed solution concentration of -carotene injected in the SCCO2 antisolvent apparatus system. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It confirmed that the -carotene that dissolved in DCM solvent was not change after recrystallization process by SCCO2. Like the particle formation from other chemical compounds by SCCO2 antisolvent [24][25][26], the particles formation from -carotene solution by SCCO2 antisolvent may be affected by the feed solution concentration of -carotene injected in the SCCO2 antisolvent apparatus system. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The flow diagram was shown in Figure 1. The detail operating process was described in our previous work [18]. In brief, carbon dioxide was purified and liquefied firstly and continuously introduced into the precipitation tank through an annular gap nozzle.…”
Section: Equipment and Operatingmentioning
confidence: 99%
“…Cefquinome concentration, feeding speed of solution, precipitation pressure, and temperature were selected as the factors of the experiment, and the level range of each factor was determined as shown in Table 1. All of these were selected based on the results of preliminary experiments and related study [18,19,21]. The median diameter ( 50 ) of particles acted as the dependent variable changing with these factors.…”
Section: Equipment and Operatingmentioning
confidence: 99%
See 1 more Smart Citation
“…Targeted drug delivery increases the drug quantity at the target site while simultaneously decreasing the systemic load to other body regions. Alternative dosage forms that provide this capacity include liposomes and nanoparticles (Fu et al, 2013 ; Kefeng et al, 2015 ). Lung-targeted drug delivery systems can deliver drug to the lung via inhalation or intravenous administration (Villara et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%